1987
DOI: 10.1016/0092-8674(87)90013-4
|View full text |Cite
|
Sign up to set email alerts
|

Yeast mitochondrial RNA polymerase is homologous to those encoded by bacteriophages T3 and T7

Abstract: Analysis of the nucleotide sequence of the genetic locus for yeast mitochondrial RNA polymerase (RPO41) reveals a continuous open reading frame with the coding potential for a polypeptide of 1351 amino acids, a size consistent with the electrophoretic mobility of this enzymatic activity. The transcription product from this gene spans the singular reading frame. In vivo transcript abundance reflects codon usage and growth under stringent conditions for mitochondrial biogenesis and function results in a several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
233
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(240 citation statements)
references
References 43 publications
5
233
0
Order By: Relevance
“…Several key enzymes involved in mtDNA maintenance are closely related to their prokaryotic counterparts; these include mitochondrial RNA polymerase (3,21), SSB protein (4,9,20,31), the high-mobility-group-box DNA binding protein mitochondrial transcription factor A (25), and the catalytic subunit of DNA pol ␥ (17,26,27,34). Nevertheless, the observation that the small subunit of DNA pol ␥ is related to prokaryotic aminoacyl-tRNA synthetases is surprising, since the latter represent a different class of enzyme involved in nucleic acid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Several key enzymes involved in mtDNA maintenance are closely related to their prokaryotic counterparts; these include mitochondrial RNA polymerase (3,21), SSB protein (4,9,20,31), the high-mobility-group-box DNA binding protein mitochondrial transcription factor A (25), and the catalytic subunit of DNA pol ␥ (17,26,27,34). Nevertheless, the observation that the small subunit of DNA pol ␥ is related to prokaryotic aminoacyl-tRNA synthetases is surprising, since the latter represent a different class of enzyme involved in nucleic acid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrated that spontaneous suppressor mutations partially rescuing the functioning of the mitochondrial genetic system in degradosome-deficient suv3⌬ strains occur in the MTF1 (YMR228W) and RPO41 (YFL036W) genes encoding the two subunits of the mitochondrial RNA polymerase (Kelly et al, 1986;Masters et al, 1987;Jang and Jaehning, 1991;Ulery and Jaehning, 1994). They are temperature-sensitive, recessive, partial loss-offunction (hypomorphic) mutations that reduce the transcrip- tion rate at normal temperature and nearly abolish the mitochondrial RNA polymerase function at elevated temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The SDB9 strain, compared with the parental strain BWG1, contained the G2932T substitution in the RPO41 gene, resulting in the V978F mutation in the amino acid sequence. Neither of these mutations has been previously described, they are both located in regions of the Rpo41p sequence displaying homology to the T3 and T7 phage RNA polymerases (Masters et al, 1987). .…”
Section: The Suppressor Mutations Are Novel Single Amino Acid Substitmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast mtRNA polymerase represents a nuclear encoded single subunit enzyme of 145 kDa which requires a specifity factor for promoter recognition, also coded in the nucleus (4)(5). The core polymerase displays strong homology with bacteriophage RNA polymerases (6). No eubacteria-like polymerase genes have been found in any of the mitochondrial genomes sequenced so far, including the first total sequence of a higher plant mitochondrial genome from Arabidopsis thaliana (7).…”
Section: Introductionmentioning
confidence: 99%